Short-term effect of crunch exercise frequency on abdominal muscle endurance - Juan-Recio, C.; López-Vivancos, A.; Moya, M.; Sarabia, J. M.; Vera-Garcia, F. J. (The Journal of Sports Medicine and Physical Fitness, 2015)
Despite core exercise programs are broadly used to increase muscle function and to promote low back health, there is a lack of scientific evidence on some of the most important characteristics of trunk exercise programs, as for example training frequency. This study aimed to compare the short-term effect of training frequencies of 1, 2 and 3 days per week (d/wk) on abdominal muscle endurance in untrained adolescents. One hundred and eighteen high-school students (59 men and 59 women) with no previous experience in structured abdominal exercise programs were assigned randomly to groups that trained 1 d/wk (G1; N.=21), 2 d/wk (G2; N.=27), 3 d/wk (G3; N.=23), or to a control group (CG; N.=47) that did not train. The training groups performed crunch and cross-crunch exercises 1, 2 or 3 d/wk during six weeks. Before and after the training period, the bench trunk-curl test (BTC test) was carried out to assess abdominal muscle endurance. Men obtained higher BTC test scores than women before and after training. Training frequencies of 1, 2 and 3 d/wk provided a significant increase in BTC test scores; however, no significant differences between the three groups' scores were found after training. Therefore, a small dose of crunch exercise training (1 d/wk) may be sufficient stimulus to increase abdominal endurance in untrained male and female adolescents, at least during the first weeks of an abdominal exercise program, which seems a very relevant finding in terms of time-cost efficiency.